Interaction of droplets and carbon particles exposed to a high-temperature air counterflow - Islamova A. G. Anastasiya Gomilievna; Kropotova S. S. Svetlana Sergeevna; Klimenko A. Andrey; Shulyaev S. A. Stanislav Antonovich (2026, 2026)
Title screen